EFFECT ON GROWTH AND MUSCLE CONTENTS OF TURBOT (Scophthalmus maximus) USING DIETS WITH DIFFERENT LEVELS OF FAT, TOCOPHEROL AND L-CARNITINE. - Fernández-Pato, Carlos; Martínez-Tapia, Inmaculada; Sola, Esperanza (2013)
This work studies growth in weight of 10 groups of turbot (S. maximus) fed on a diet in which fat, ó-tocopherol or L-Carnitine have been incorporated, or in other cases a combination of the these. Significant differences between the groups were found, which were determined through a MANOVA with a design of repeated measurements, being p<O.OOl for all groups. Those which presented higher growth ingested a dose of 300 mg of l-Carnitine and those presenting lower growth ingested fat (16% of dry food), without any other factors added. The protein and lipid content analyses in carcass and liver showa difference of fat accumulation, with values varying from 7 to 20% of humid weight for those treated with l-Carnitine, ó-tocopherol, and fat respectively according to treatment.